2015
DOI: 10.1061/(asce)ps.1949-1204.0000198
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Operation of Water Distribution Networks Considering Equanimity and Justice Principles

Abstract: Water shortages cause intermittent operation of distribution networks in many developing countries. Under limited economic resources and frequent water shortages, the expansion of water supply for municipal use is slow and sometimes infeasible, hence supply management becomes a viable solution for operating water supply networks. One form of demand management is intermittent supply, wherein some parts of the water supply network are cut off from service during certain times and the entire network is in service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Many of the conditions of intermittency, like low prices, broad network distribution, and rationing, are intended to deliver water as broadly and inclusively as possible. Recent research has calculated optimized distribution schedules for intermittent supply in an effort to support equanimity and justice [16,104]. However, studies have shown that poor communities within such systems shoulder many additional coping expenses, many of which are not visible to system operators [94,127].…”
Section: )mentioning
confidence: 99%
“…Many of the conditions of intermittency, like low prices, broad network distribution, and rationing, are intended to deliver water as broadly and inclusively as possible. Recent research has calculated optimized distribution schedules for intermittent supply in an effort to support equanimity and justice [16,104]. However, studies have shown that poor communities within such systems shoulder many additional coping expenses, many of which are not visible to system operators [94,127].…”
Section: )mentioning
confidence: 99%
“…In an intermittently supplied system, the hydraulic conditions associated with consumer behavior and strategic decisions result in inequitable water allocation [19,29,30,[64][65][66][67].…”
Section: Social and Political Problems Imentioning
confidence: 99%
“…These problems lead water utilities to question the relevance of installing meters for this type of supply, but their absence generates other complications such as the obligation to introduce flat-rate or roughly evaluated billing [63], and the difficulty of estimating network performance. In an intermittently supplied system, the hydraulic conditions associated with consumer behavior and strategic decisions result in inequitable water allocation [19,29,30,[64][65][66][67].…”
mentioning
confidence: 99%
“…Since their introduction in the 19th century, the health benefits of CWS have been well recognized [ 3 ]. Studies continue to demonstrate that IWS deliver water less equitably and are more likely to recontaminate the finished water than CWS [ 4 , 5 ]. Yet 41% of piped water systems in lower and middle-income countries operate intermittently [ 2 ].…”
Section: Introductionmentioning
confidence: 99%